Sincerity, Honor or Salary in Education - Muhammad Azryan Syafiq; Noorazmah Hidayati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Education plays a significant role in Islam, serving as a means to draw closer to Allah, instill good character, and improve the relationship between humans and the environment. In this context, sincerity, honor, and compensation for educators become relevant topics of discussion. This article explores the Islamic perspective on these three aspects and how they form the foundation of sustainable education. Through a review of the Qur'an and Hadith literature, as well as text analysis and interpretation, this article highlights the importance of sincerity in carrying out educational tasks and providing adequate recognition to educators. Islam views education as a long-term investment for both worldly and spiritual purposes, by providing honorable compensation to educators as an investment in the future of the community and to gain blessings in the Hereafter.